2020
DOI: 10.3389/fnagi.2020.583884
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chronic Inflammatory Bone and Joint Disorders in the Pathogenesis and Progression of Alzheimer's Disease

Abstract: Late-onset Alzheimer's Disease (LOAD) is a devastating neurodegenerative disorder that causes significant cognitive debilitation in tens of millions of patients worldwide. Throughout disease progression, abnormal secretase activity results in the aberrant cleavage and subsequent aggregation of neurotoxic Aβ plaques in the cerebral extracellular space and hyperphosphorylation and destabilization of structural tau proteins surrounding neuronal microtubules. Both pathologies ultimately incite the propagation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 382 publications
(373 reference statements)
0
11
0
Order By: Relevance
“…Metals with neurotoxic properties have also been detected in the brain and cerebrospinal fluid from patients with neurodegenerative diseases, as they can cross the blood-brain barrier (Choi and Zheng, 2009 ). Inflammatory cytokines, including tumor necrosis factor-α, interleukin-1β, and interleukin-6, have been postulated to be involved in AD, PD, and osteoporosis (Zhang and Tian, 2014 ; Culibrk and Hahn, 2020 ). Third, oxidative stress and mitochondrial oxidative damage caused by aging may play a central role in these diseases because the risks of osteoporosis, AD, and PD increase significantly with age (Mattson et al, 1995 ; Yakunin et al, 2014 ; Domazetovic et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metals with neurotoxic properties have also been detected in the brain and cerebrospinal fluid from patients with neurodegenerative diseases, as they can cross the blood-brain barrier (Choi and Zheng, 2009 ). Inflammatory cytokines, including tumor necrosis factor-α, interleukin-1β, and interleukin-6, have been postulated to be involved in AD, PD, and osteoporosis (Zhang and Tian, 2014 ; Culibrk and Hahn, 2020 ). Third, oxidative stress and mitochondrial oxidative damage caused by aging may play a central role in these diseases because the risks of osteoporosis, AD, and PD increase significantly with age (Mattson et al, 1995 ; Yakunin et al, 2014 ; Domazetovic et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with HPA axis hyperactivity and glucocorticoid resistance, finally leading to uncontrolled inflammation [ 86 , 113 ]. Moreover, acute and chronic inflammation may aggravate existing neurodegenerative diseases [ 114 , 115 , 116 , 117 , 118 ]. Meta-analyses showed that levels of circulating pro-inflammatory cytokines (TNF, IL-1β and IL-6) are up-regulated in AD patients compared to age-matched control subjects and increased inflammation might even precede the outbreak of the disease [ 119 , 120 ].…”
Section: Microglia Are Under the Influence Of Peripheral Inflammationmentioning
confidence: 99%
“…While the gene expression data shows that the response to CHIKV involves changes in neurotransmission and immune response, clinical trials have shown that dysregulation of the inflammatory response can remodel neurotransmission, leading the changes in mood and cognition [ 13 , 65 , 66 ]. The reduced expression of ACHE has been linked to depression and cognitive deficits in human studies [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%